PENENTUAN BESARNYA PAJAK PENGHASILAN PADA PT. CAHAYA PERMATA AJRIYA DI SAMARINDA - Yulian Anwar, Zulfikar (EKONOMIA, 2012)
In the field of construction businessgovernment issued Government RegulationNo. 140 of 2000 on Income Tax on Incomefrom Construction Services, the Minister ofFinance       No.      559/KMK.04/2000     datedDecember 26, 2000 About Tax on Incomefrom Construction Services and SE-13 /PJ.42/2002 dated July 22, 2002 on theImplementation     of      the       Income       TaxTreatment of Income from ConstructionServices. Further to the uniformity of thetechnical regulation on the implementationof income tax reporting by the businessentity (corporation) is a publication of Bookof Financial Accounting Standards No. 46(PSAK No..46).The Company has not imposed PSAK. 46 inthe calculation of corporate income tax andthis will affect the company's financialstatements.